Picking Up the Pieces: What Next for Asia-Pacific Trade Policy - Rogerson, Evan (2017)
The Trans-Pacific Partnership negotiations have been a primary focus for trade negotiators in Southeast Asia and the wider region. Now that the Trump administration has rejected TPP, the outlook for trade policy is uncertain. Can TPP be revived in some form? Can RCEP step in? Do bilateral deals become the new norm? And is there any future in multilateral negotiation?